Two-dimensional halide perovskite as β-ray scintillator for nuclear radiation monitoring - Dejian Yu (Nature Portfolio, 2020)
Efficient radiation monitoring ensures safety in nuclear power, but beta-ray scintillators should be developed for use near a highly radioactive and hot reactor. Here, the authors report a two-dimensional halide perovskite-based beta-ray scintillator with high irradiation hardness and thermotolerance.